2014
DOI: 10.1186/1710-1492-10-47
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immunization with ovalbumin or Dermatophagoides pteronyssinus has opposing effects on FcγRIIb expression on offspring B cells

Abstract: BackgroundOver the last decade, our group has demonstrated that murine preconception immunization with allergens has a protective effect on allergy development in offspring. The murine model used in the present study allowed us to compare allergy induction by ovalbumin (OVA) and dust mite extract from Dermatophagoides pteronyssinus (Dp).FindingsFemale mice were immunized with OVA or Dp. Pups from immunized and non-immune mothers were immunized at 3 days old (do) with the same antigen used for the maternal immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The maternal immunization protocol with OVA suppressed the offspring allergic response, sensitizing the offspring at a similar humoral level as previously observed by our laboratory in a similar mouse model [5, 13]. The protection induced by maternal immunization in murine models was previously evidenced by other researchers [15].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The maternal immunization protocol with OVA suppressed the offspring allergic response, sensitizing the offspring at a similar humoral level as previously observed by our laboratory in a similar mouse model [5, 13]. The protection induced by maternal immunization in murine models was previously evidenced by other researchers [15].…”
Section: Discussionsupporting
confidence: 81%
“…2 c). Our laboratory previously reported that the maternal Dermatophagoides pteronyssinus (Dp) immunization protocol induces an opposite effect on FcγRIIB expression in offspring B cells compared with OVA [ 13 ], and we thus evaluated the induction of B10 cells in this model. Even at a higher dose of allergen than that used in our previous experiments, maternal Dp immunization did not induce B10 cells in offspring, and the opposite effect on FcγRIIB expression was maintained (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has already reported that the maternal immunization protocol with OVA in WT mice could down-regulate the intracellular IL-4 production on offspring, suggesting a Th2 inhibition [14], and four years later, we also observed that maternal immunization with a dust mite extract ( Dermatophagoides pteronyssinus ) could not induce the same cytokine and phenotype profile in offspring cells [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the last 15 years, our group has investigated adoptive maternal–fetal immune interactions in the context of allergy regulation . In 2014, the authors suggested that maternal immunization could influence intrathymic maturation of lymphocytes on offspring .…”
Section: Introductionmentioning
confidence: 99%